Hydroxychloroquine Therapy Led to the Diagnosis of Glucose-6-Phosphate Dehydrogenase (G6PD) Deficiency in an Elderly Patient with COVID-19 Involvement: A Case Report and Review of the Literature - Razieh Taghizadeh-Sarvestani; Hamid Reihani; Ali Ghanei-Shahmirzadi; Alireza Keshtkar; Parsa Yazdanpanahi (Case Reports in Medicine)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common RBC abnormality, affecting 400 million people globally. Neonatal jaundice, hemolytic anemia, icteric skin, dark urine, and fever are usually the primary signs of this condition, which is generally diagnosed between the ages of infancy and 16 years old. Therefore, its first manifestation in old age is an unexpected phenomenon. Here, we present the case of a 70-year-old man with no past medical history of G6PD deficiency that was admitted to our hospital due to COVID-19 infection and developed acute hemolytic anemia while receiving hydroxychloroquine (HCQ) medication for COVID-19-related pneumonia.